FREQUENCY OF DOUBLE LUMEN CATHETER RELATED INFECTIONS IN HEMODIALYSIS PATIENTS - Muhammad Shoaib1, Bhagwan Das2, Muhammah Ali Suhail3, Rafia Memon4, Kishor Kumar5, Babeeta Hinduja6, Afreen Naz7 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
To determine the frequency of catheter associated infections in cases of hemodialysis using double lumen hemodialysis catheters. STUDY DESIGN: Descriptive cross-sectional study. PLACE AND DURATION OF STUDY: Department of Nephrology (Dialysis Unit), Liaquat University of Medical & Health Sciences Jamshoro from 3rd June 2019 to 2nd December 2019. METHODOLOGY: One hundred and nineteen cases with end stage renal disease on maintenance hemodialysis having age 16 to 70 years of either gender who met inclusion criterion were included in the study. All hemodialysis patients who treated with double lumen hemodialysis catheters were assessed for catheter related infections. All the collected data were recorded. RESULTS: The average age was 55.8±10.34 years, mean duration on catheter insertion was 27.4±6.05 days, 70 (58.8%) patients were male and 49 (41.2%) were female. Catheters related infection was found in 61 (51.3%) patients. CONCLUSION: The catheter associated infections are alarmingly high and a major contributing factor for morbidity and mortality in patients undergoing hemodialysis using double lumen hemodialysis catheters.